Analysis of the small non-protein-coding RNA profile of mouse spermatozoa reveals specific enrichment of piRNAs within mature spermatozoa. Issue 12 (2nd December 2017) - Hutcheon, Kate; McLaughlin, Eileen A.; Stanger, Simone J.; Bernstein, Ilana R.; Dun, Matthew D.; Eamens, Andrew L.; Nixon, Brett
ABSTRACT: Post-testicular sperm maturation and storage within the epididymis is a key determinant of gamete quality and fertilization competence. Here we demonstrate that mouse spermatozoa possess a complex small non-protein-coding RNA (sRNA) profile, the composition of which is markedly influenced by their epididymal transit. Thus, although microRNAs (miRNAs) are highly represented in the spermatozoa of the proximal epididymis, this sRNA class is largely diminished in mature spermatozoa of the distal epididymis. Coincident with this, a substantial enrichment in Piwi-interacting RNA (piRNA) abundance in cauda spermatozoa was detected. Further, features of cauda piRNAs, including; predominantly 29–31 nts in length; preference for uracil at their 5' terminus; no adenine enrichment at piRNA nt 10, and; predominantly mapping to intergenic regions of the mouse genome, indicate that these piRNAs are generated by the PIWIL1-directed primary piRNA production pathway. Accordingly, PIWIL1 was detected via immunoblotting and mass spectrometry in epididymal spermatozoa. These data provide insight into the complexity and dynamic nature of the sRNA profile of spermatozoa and raise the intriguing prospect that piRNAs are generated in situ in maturing spermatozoa. Such information is of particular interest in view of the potential role for paternal sRNAs in influencing conception, embryo development and intergenerational inheritance.